Copy the Master Strategy with Synectic Model Assisted by Puzzle Media on Motivation and Learning Outcomes in Writing Imaginative Stories - Sukarman, Lufi Afita Kardina; Hartono; Ari Kusmiatun (LPPM Undiksha, 2025)
Students' low writing skills are generally caused by suboptimal teaching methods implemented by teachers. This study aims to analyze the impact of the